The effect of high loading rate to tensile strength for mild steel by using Hopkinson Bar technique - Mohd Shahiddin, Suhadi; Rakhmad Arief, Siregar; Shah Fenner Khan; Ahmad Yusri; Abd Hamid, Adom (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 1111th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.